Estrutura e dinâmica sazonal da comunidade de bactérias planctônicas em ambientes da planície de inundação do alto rio Paraná. - Chiaramonte, Josiane Barros (2013)
Differences in bacterial community might be related to many factors such as nutrients contends and interaction with other microorganisms. Differences in how the bacterial community is distributed among sites might impact the nutrient cycle to the ecosystems. The aim of this study was to analyze the distribution of bacterial community in different sites of the Upper Paraná River floodplain about the existence of differences in bacterial community structure among sites and its correlation with dissimilarities of abiotical conditions. And then, investigate how bacterial community structure changes in a hydrological cycle. The samples were performed in 36 sites of Paraná River floodplain, classified as connected and unconnected lakes and channels, distributed among three main rivers that compound this floodplain. Bacterial community structure was analyzed considering bacterial total density and relative abundances of the main domains Bacteria and Archaea, and subdivisions of the phyla Proteobacteria (Alpha-proteobacteria, Beta-proteobacteria, Gamma-proteobacteria) and Cytophaga-Flavobacterium group; that were estimated by fluorescent in situ hybridization. The structure of bacterial community differed according to the river´s characteristics in which the ambient are connected to. Differences in chlorophyll-a, total and ammoniacal nitrogen and orthophosphate were the mainly limnological variables that determines de bacterial community structure among the sites. The influence of the flood pulse in the bacterial community was analyzed in every three months samples (from December/2010 to September/2011), in twelve sites in upper Paraná River floodplain. We concluded that the flood pulse changes more significantly the bacterial community structure than the limnological differences among the rivers that compose the floodplain. Furthermore, in despite to what is observed to other planktonic communities the flood pulse decreases bacterial diversity during high water period. These results observed in a study with large bacterial groups suggest that a greater taxonomic refinement, the results could enlighten even more about how bacterial structure is influencing nutrient cycles in floodplain systems.